Generation and characterization of transcription activator-like effector nucleases - Waltl, Laura; Justus Liebig University Giessen (My University, 2016)
Designer nucleases are developed to modify the genome in various organisms, and are promising molecular tools for the advancement of gene therapy. They should introduce only one specific double-strand or single-strand break in a complex genome in order to trigger the DNA repair mechanisms of the cell such that the DNA damage is repaired by homologous directed repair (HDR) or non-homologous end joining (NHEJ), an error-prone repair mechanism that can be applied to knock out genes. With the addition of an external DNA fragment, HDR can be exploited to correct or add a gene. Transcription activator-like effector (TALE) nucleases belong to a platform of designer nucleases and are known to be highly specific, efficient and easy to customize for any given target. Nevertheless, there is still a need to improve the accuracy of TALE nucleases for their reliable application in vivo. To this end, off-target activity should be avoided without compromising cleavage efficiency. This can be achieved by optimization of the catalytic domain as well as by improving the binding domain. The subjects of this comparative study are the homing endonuclease I-SceI, the widely used TALE-FokI fusion protein, the new RNA guided Cas9 nuclease and our recently developed TALE-PvuII variants as well as the TALE-MutH fusion protein, whose nuclease domain is a sequence- and strand-specific nickase. In the study we have analyzed the toxicity and cleavage efficiency of these specific nucleases in a yeast based single-strand annealing assay as well as in vitro. The present study also focus on the characterization of the in vitro binding mechanism of TALE. Binding characteristics of AvrBs3(Delta N152-C28) were analyzed via anisotropy measurements, specific singleand double-labeled TALE variants were designed and DNA::Protein complexes were analyzed employing FRET measurements.We gained labeled variants remaining their binding characteristics and enables the investigation of the in vitro binding mechanism of TALE proteins.Our results demonstrate convincingly that the monomeric TALEMutH nickase displays less toxicity in Saccharomyces cerevisiae compared to the widely used dimeric TALE-FokI nuclease and is able tointroduce the repair of the DNA damage via single-strand annealing as efficient as I-SceI, the gold standard for cleaving genomic DNA. To improve the design of TALE-MutH nickases, we analyzed the cleavage behavior on various specific loci in vitro and in vivo. The results presented show that the TALE-MutH fusion protein is a promising programmable nickase for in vivo applications and these results were confirmed by a TALE-MutH addressing a relevant therapeutic gene.

Konstruierte Nukleasen wurden entwickelt um das Genom in verschiedenen Organismen zu modifizieren und sind viel versprechende Werkzeuge zur Weiterentwicklung von effizienten Gentherapien. Spezifische Nukleasen sollten einen spezifischen Doppel- oder Einzelstrangbruch in dem komplexem Genom induzieren und hierdurch den DNA Reparaturmechanismus der Zelle auslösen. Die DNA wird hierbei durch homologous directed repair (HDR) oder non-homologous end joining (NHEJ) repariert. NHEJ ist ein zu Fehlern neigender Reparaturmechanismus und kann zur Ausschaltung eines Gens angewendet werden. Mit Hilfe eines externen DNA Fragments kann HDR zur Korrektur oder zum Hinzufügen eines Gens genutzt werden. Transcription activator-like effector (TALE) Nukleasen bilden eine Gruppe der konstruierten spezifischen Nukleasen und sind aufgrund ihrer hohen Spezialität, Effizienz und einfachen Anfertigung für beliebige adressierte Sequenzen bekannt. Dennoch werden weitere Verbesserungen benötigt um die Genauigkeit von TALENs für die zuverlässige in vivo Anwendung zu gewährleisten. Hierbei müssen off-target Ereignisse vermieden werden ohne dabei die Spaltaktivität zu kompromittieren. Dies kann durch die Optimierung der katalytischen Domäne, sowie durch die Verbesserung der Bindungsdomäne erreicht werden. Die Themen dieser vergleichenden Arbeit sind die Homing Endonuklese I-SceI, das weit verwendeten TALE-FokI Fusionsprotein, die neuartige RNA gesteuerte Cas9 Nuklease und die erst kürzlich etablierten TALE-PvuII Varianten, sowie das TALE-MutH Fusionsprotein. Letzteres besitzt eine Nuklease Domäne, welche eine Sequenzund Strand-spezifische Nickase darstellt. In der Arbeit haben wir die Toxizität und Spaltaktivität dieser spezifischen Nukleasen in Hefe durch einen single-strand annealing assay und in vitro analysiert. Die aktuelle Studie konzentriert sich auch auf die in vitro Charakterisierung des Bindungsmechanismus von TALE. Die Bindungscharakteristika von AvrBs3(1 N152-C28) wurden durch Anisotropiemessungen bestimmt, spezifisch einzel- oder doppelt-markierte TALE Varianten wurden hergestellt und DNA::Protein Komplexe wurden durch FRET-Messungen untersucht. Wir konstruierten fluoreszenzmarkierte Varianten die ihre Bindungscharakteristiken behielten und somit die Untersuchung der in vitro Bindungsmechanismen ermöglichen. Die Ergebnisse zeigen dass die monomere TALE-MutH Nickase eine geringere Toxizität in Saccharomyces cerevisiae im Vergleich zu der dimer TALE-FokI Nuklease aufweist. Des weiteren ist TALE-MutH zur Reparatur des DNA Schaden durch single-strand annealing fähig und hierbei genauso effizient wie der Goldene Standard I-SceI. Zur Verbesserung des TALE-MutH Designs wurde das Spaltverhalten auf verschiedene Loci in vitro und in vivo getestet. Die präsentierten Ergebnisse zeigen dass das TALE-MutH Fusionsprotein eine vielversprechende Nickase für in vivo Anwendungen darstellt mit welchem auch therapeutisch relevante Gene adressiert werden können.
Generierung und Charakterisierung von Transcription activator-like effector Nukleasen
Keywords: ddc:570